Three strikes and you're dead : a novel - Bain, Donald, 1935-2017 (Fletcher, Jessica. Murder, she wrote., 2006)
Visiting her old friends Judge Jack and Meg Duffy in Arizona, Jessica watches their foster son hit the winning run for the Mesa Rattlers in a AA league playoff game. She and the Duffys are thrilled at Ty Ramos's success, but team owner Harrison Bennett is not. His son Junior and Ty are bitter rivals, and the tension at the team dinner later that evening threatens to empty the dugouts. By the next morning, Junior Bennett is dead, and Ty is the prime suspect. Jessica finds it hard to believe that such a fine young man would wreck his life in a moment of anger-and when she starts looking into the Rattlers' recent season, she finds out that for some people, baseball is more than just a game.